CHEMISTRY LEARNING OF REDOKS MATERIAL WITH REDOX GAME AS LEARNING MEDIA WHILE CORONA PANDEMIC CHEMICAL - Umah, Putri Amiratul; lutfi, achmad (JCER (Journal of Chemistry Education Research), 2024)
This research aims to determine the effectiveness of Redox learning media as measured by looking at student learning outcomes and students' responses after using Redox game media on redox material. In this study using a one group pretest-posttest research design, where participants will be given a pretest before using game media and also given posttest after the use of game media. The game media were tested on 28 students in the XII mathematics and science 3 class at public senior high school 2 Ngawi. The results of the study showed that the learning outcomes of students after using the Redox game media had increased with classical completeness reaching 85.7%. The score obtained by students when doing a pretest is 23.9 and posttest is 80.8 so it shows an increase that is tested with an N-gain score of 0.7 which is in the medium category. In addition, the response of students after using Redox game media was 87.88%, indicating that Redox game media can be used as instructional alternatives in chemistry learning.